Challenges of Online Learning in Kandahar City, Afghanistan - Alinaqi Mohammadi; Shekiba Hilal; Zakia Hanif; Salman Ali Nabavi (Randwick International of Education and Linguistics Science Journal, 2024)
Despite the growing need for online education in Afghanistan and especially in Kandahar city, unfortunately this form of learning has not been well developed here. The findings show that online learning, in addition to growing needs and opportunities, faces many challenges in Afghanistan, especially in Kandahar city. In this context, this research has been done to investigate the fundamental factors challenging online learning in Kandahar city. Keeping in mind the previous studies, in order to achieve the goals of this research, a purposeful sampling method was used to find and analyze the key issues raised, and as a result, the basic problems facing online learning in Kandahar city were investigated as much as possible. In the following, the necessary suggestions are also presented so that, by implementing it, the relevant practitioners and policy makers will solve the existing problems and provide the basis for sustainable and all-round development of Kandahar city, Afghanistan and the region.